PERANCANGAN UI/UX PADA APLIKASI MUSIC POPULER DENGAN METODE DESIGN THINKING BERBASIS ADOBE XD - Fatekha, Putri; Khozin, Muhammad; Novitaningrum, Dian (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2025)
Popular music apps are becoming increasingly popular among the masses, and the demand for meaningful personal digital entertainment is increasing. This study aims to develop a music app that provides the best user experience through smart visualization, personalized features, and online access. The methodology chosen for developing this app is “Think About It,” which consists of five stages: Empathy, Explanation, Ideation, Prototype, and Testing. Each stage is designed to understand user needs, create innovative solutions, and provide a user-friendly interface. The findings show that the developed music app meets user needs such as easy access to music, relevant recommendations, and comprehensive search capabilities. Testing with end users has resulted in high usage rates, although there are still some areas for improvement, such as reducing click-through error rates and simplifying navigation. This study concluded that the developed tool met many of the needs of the users. However, more iterations are still needed to improve the interface and improve usability. We hope that this study can serve as a reference for creating modern digital music tools that better meet the needs of modern users.